พฤติกรรมการรังแกบนโลกไซเบอร์ของเยาวชนในสามจังหวัดชายแดนใต้ - สิทธิชัย, ฤทัยชนนี; ตุดเกื้อ, ธันยากร (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 28 No 1 (2560): Academic Services Journal, Prince of Songkla University, 2017)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาพฤติกรรมการรังแกบนโลกไซเบอร์ สาเหตุการเกิดพฤติกรรมการรังแกและลักษณะวิธีการจัดการของเยาวชนในสามจังหวัดชายแดนใต้ กลุ่มตัวอย่างจำนวน 27 คน เป็นผู้ถูกรังแกและรังแกผู้อื่นบนโลกไซเบอร์ คัดเลือกกลุ่มตัวอย่างด้วยเทคนิคการบอกต่อ (Snowball Technique) เป็นการศึกษาเชิงคุณภาพ ใช้แบบสัมภาษณ์กึ่งโครงสร้าง และสนทนากลุ่ม ผลการวิจัยพบว่า เยาวชนส่วนใหญ่รู้จักและเข้าใจพฤติกรรมการรังแกบนโลกไซเบอร์ในระดับดีมาก ทั้งการประสบกับตนเองและเห็นบุคคลอื่นปฏิบัติจนเป็นเรื่องปกติ โดยแบ่งออกเป็น 5 ด้าน ได้แก่ 1) การนินทาหรือด่าทอผู้อื่น 2) การหมิ่นประมาทผู้อื่น 3) การแอบอ้างชื่อผู้อื่นในด้านลบ 4) การนำความลับที่เป็นข้อมูลส่วนตัวหรือข้อมูลของผู้อื่นไปเปิดเผย และ 5) การลบหรือบล็อกผู้อื่นบนโลกไซเบอร์ เยาวชนส่วนใหญ่เลือกกระทำกับบุคคลอ่อนแอกว่า เครื่องมือที่เลือกใช้ในการรังแกผู้อื่นบนโลกไซเบอร์ ผ่านทางสื่อสังคมออนไลน์ Facebook และ Line มากที่สุด รองลงมาได้แก่ Messenger, Instagram, Twitter, BeeTalk WeChat, SocialCam, and YouTube รวมทั้งการรับส่งข้อความผ่านโทรศัพท์มือถือ สาเหตุส่วนใหญ่พบว่า มาจากปัญหาด้านครอบครัว ด้านเกมและภาพยนตร์ที่ชื่นชอบ ด้านเทคโนโลยีที่สามารถใช้อินเทอร์เน็ตได้ตลอดเวลาทุกที่ ด้านความภาคภูมิใจในตนเองต่ำ ด้านความคับข้องใจ และด้านอิทธิพลความรุนแรงจากเพื่อน วิธีการจัดการเมื่อเยาวชนตกเป็นเหยื่อของการถูกรังแกบนโลกไซเบอร์ ส่วนใหญ่จะเงียบเก็บไว้คนเดียว ต่อมาใช้วิธีการลบหรือบล็อก ตอบโต้หรือรังแกกลับทันทีในแบบที่โดนรังแก วิธีการพูดคุย เพื่อเจรจาต่อรอง วิธีการอดทน วิธีการหยุดหรือเลิกใช้เครือข่ายสังคมออนไลน์นั้น วิธีการที่เยาวชนไม่เลือกใช้ คือ การปรึกษาพ่อแม่ หรือญาติพี่น้อง มีแต่บางคนปรึกษาเพียงเพื่อนสนิทเท่านั้น คำสำคัญ: การรังแกบนโลกไซเบอร์, เยาวชน, สามจังหวัดชายแดนใต้   This research aims to study the cyberbullying behaviors as well as the causes and copes with it among young people in three southern provinces. The data was collected from youth in the three southern provinces who had experience in cyberbullying. The samples were twenty seven victimization and perpetrator, by using the Snowball Technique. This study was qualitative research which the instrument was semi-structure interview. The focus group interview was employed. The research found that most of young people identify and understand cyberbullying behavior both by their own experience and used to perceive from others as their habits. Cyberbullying was divided in to five aspects. There were 1) gossips or insulting 2) slanders 3) negative imposture of others. 4) spreading confidential information and 5) remove or block others on cyberspace. Most of the weak youth were the target of cyber victimization. Furthermore, it was found that the tool that the youth used for cyberbullied victims on cyberspace was a program that had been used over the internet. The most popular one were Facebook and Line, followed by Messenger, Instagram, Twitter, BeeTalk WeChat, SocialCam, and YouTube as well as the messages via mobile phones. Moreover, the causes of cyberbullying were from their family, games and movies, internet access for anytime and anywhere, low self-esteem, frustration, violence that influence from friends. Furthermore, for coping of cyberbullyings, youth deals with several and different ways. Some they kept quiet later delete or block others, responses or cyberbullied back, compromised, patient, stopped or cancelled accessing to social networking. Furthermore, the coping that youth rarely deal with cyberbullying was consulting their parents, relatives. However, some consulted their close friends. Keywords: cyberbullying, youth, three southern border provinces